125 KHz ubiquitous RFID tag signal detector system - Fazrul Faiz, Zakaria; Anuar, Mat Safar, Ir.; Soh, Ping Jack; Syed Alwee Aljunid, Syed Junid, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/